The determinants of Strategic Information System Planning (SISP) success: A proposed framework for Small and Medium-Sized Enterprises (SMEs) - Raja Mohd Ali, Raja Haslinda; Mohamad, Rosli; Tretiakov, Alexei (IBIMA Publishing, 2013)
The growing importance of Information System (IS) to support business operation demands for adequate IS planning.Good IS planning enables organizations to closely align the IS and strategic business objectives.Such alignment ultimately ensures organizations to gain competitive advantages from IS-related investment.Despite extensive works to understand SISP practices in large organizations, works are still limited in the context of Small and Medium Enterprise (SMEs).This issue is worth further investigation in view of the increasing importance of IS to support many facets of the SMEs operation.More importantly, due to inherent resource constraints among SMEs to invest in IS, top management commitment as well as user participation in IS planning activities are getting more crucial.This study, therefore proposes a framework to assess the effect of top management commitment and user participation on SISP success. The findings are of relevance for firm’s top management in ensuring SISP success.